Whole-Exome Sequencing in Searching for New Variants Associated With the Development of Parkinson’s Disease - Shulskaya, Marina V.; Alieva, Anelya Kh.; Vlasov, Ivan N.; Zyrin, Vladimir V.; Fedotova, Ekaterina Yu.; Abramycheva, Natalia Yu.; Usenko, Tatiana S.; Yakimovsky, Andrei F.; Emelyanov, Anton K.; Pchelina, Sofya N.; Illarioshkin, Sergei N.; Slominsky, Petr A.; et al. (Frontiers in Aging Neuroscience, 2018)
Background: Parkinson’s disease is a complex disease with its monogenic forms accounting for less than 10% of all cases. Whole-exome sequencing technology has been used successfully to find mutations in large families. However, because of the late onset of the disease, only small families and unrelated patients are usually available. Whole-exome sequencing conducted in such cases yields in a large number of candidate variants. There are currently a number of imperfect software tools that allow the pathogenicity of variants to be evaluated. Objectives: We analyzed 48 unrelated patients with an alleged autosomal dominant familial form of Parkinson’s disease using whole-exome sequencing and developed a strategy for selecting potential pathogenetically significant variants using almost all available bioinformatics resources for the analysis of exonic areas. Methods: DNA sequencing of 48 patients with excluded frequent mutations was performed using an Illumina HiSeq 2500 platform. The possible pathogenetic significance of identified variants and their involvement in the pathogenesis of Parkinson’s disease was assessed using SVS, CADD, and REVEL software. Functional evaluation was performed using the Pathway Studio database. Results: A significant reduction in the search range from 7082 to 25 variants in 23 genes associated with Parkinson’s disease or neuronal function was achieved. Eight (FXN, MFN2, MYOC, NPC1, PSEN1, RET, SCN3A, and SPG7) were the most significant. Conclusions: The multistep approach developed made it possible to conduct an effective search for potential pathogenetically significant variants, presumably involved in the pathogenesis of Parkinson’s disease. The data obtained need to be further verified experimentally.